2020
DOI: 10.1002/jpen.1982
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Development of Distal Jejunal and Duodenal Adenomas After 41 Months of Teduglutide Treatment in a Patient With Short‐Bowel Syndrome: A Case Report

Abstract: The glucagon‐like peptide‐2 (GLP‐2) analogue teduglutide is a medical treatment option for patients with short‐bowel syndrome–associated chronic intestinal failure. Because studies in mice have shown that GLP‐2 analogues may promote the growth of colonic neoplasms, surveillance colonoscopies before and during teduglutide therapy were recommended. The occurrence of small‐intestinal neoplasms has not been reported so far, except for a recent report about de novo development of hamartomatous duodenal polyps. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Après sa mise sur le marché, le téduglutide a fait l'objet de quelques études en vie réelle. Une patiente a présenté des adénomes du grêle (un dans le duodénum et un dans le jéjunum) après 41 mois de traitement [49], suggérant que des effets indésirables pourraient être observés après une durée prolongée de traitement et qu'il est important d'obtenir des facteurs prédictifs de réponse ou non au traitement.…”
Section: Discussionunclassified
“…Après sa mise sur le marché, le téduglutide a fait l'objet de quelques études en vie réelle. Une patiente a présenté des adénomes du grêle (un dans le duodénum et un dans le jéjunum) après 41 mois de traitement [49], suggérant que des effets indésirables pourraient être observés après une durée prolongée de traitement et qu'il est important d'obtenir des facteurs prédictifs de réponse ou non au traitement.…”
Section: Discussionunclassified
“…care reports showed the de novo development of upper GI adenomas in patients receiving teduglutide, gastroscopy before and during teduglutide treatment is advised. 56,57…”
Section: Laboratory Assessmentmentioning
confidence: 99%
“…Despite this recommendation, a retrospective analysis of a large population‐based commercial database found that, between 2015 and 2019, 170 adult patients with SBS‐IF were prescribed teduglutide, of whom 47% did not have a colonoscopy prior to initiating therapy 55 . As recent care reports showed the de novo development of upper GI adenomas in patients receiving teduglutide, gastroscopy before and during teduglutide treatment is advised 56,57 …”
Section: Identification Of Patients Eligible For Teduglutide Treatmentmentioning
confidence: 99%
“…40,41 Because teduglutide is a growth factor and has the ability to enhance the growth of colonic and other gastrointestinal polyps as well as accelerate cancer growth, it is contraindicated in patients with active gastrointestinal malignancies, and patients should be screened by colonoscopy before initiating treatment and periodically while on this therapy. 42 As the GLP-2 receptors are primarily expressed in the gastrointestinal tract and brain, the package insert states that the decision to continue teduglutide in patients with nongastrointestinal malignancy should be made based on benefit-risk considerations. We note, however, that the confirmatory Phase 3 STEPS trial (study of teduglutide effectiveness in parenteral nutrition-dependent short bowel syndrome subjects) report to the Food and Drug Administration included the occurrence of 1 liver cancer and 2 lung cancers among trial subjects treated with teduglutide.…”
Section: Best Practice Advice 9: Glucagon-like Peptide-2mentioning
confidence: 99%